Freedom & its discontents reflections on four decades of American moral experience - Marin, Peter (Steerforth, 1995)
His topics are diverse: the tidal chaos that is adolescence; the foolishness and hedonism of our pop therapies; the unquestioning acceptance of authority that he finds among the followers of a Tibetan Buddhist in Boulder, Colorado; a review of the Vietnam films of Francis Ford Coppola and Michael Cimino which becomes, in Marin's hands, a protracted meditation on the moral pain of the men and women who fought that war. Unifying all of these essays is his unwavering attention to the moral and ethical meanings that lie behind our actions (or lack of action) and his consistent questioning of how we go about finding the magnanimity we owe to all human life in the face of "our fears of strangeness, our hatred of deviance, our love of order and control.